The Effect of Company Growth, Profitability, Leverage, Liquidity, and Public Accounting Firm Size on Going Concern Audit Opinion with the Previous Year's Audit Opinion as a Moderating Variable (Empirical Study of Property and Real Estate Sector Companies Listed on the Indonesian Stock Exchange in 2019–2022) - Melia, Melia (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study aims to examine the effects of company growth, profitability, leverage, liquidity, and public accounting firm size on going concern audit opinions, with the previous year’s audit opinion as a moderating variable, in property and real estate sector companies listed on the Indonesia Stock Exchange. This study used 60 property and real estate sector companies listed on the Indonesia Stock Exchange during the 2019–2022 period. The results show that company growth and public accounting firm size have no effect on going concern audit opinions, while profitability, leverage, and liquidity have an effect on going concern audit opinions. The interaction test shows that the previous year’s audit opinion is unable to moderate the effects of profitability and liquidity on going concern audit opinions. However, the previous year’s audit opinion strengthens the effects of company growth, leverage, and public accounting firm size on going concern audit opinions.